ArchEnemy - Beddor, Frank (Looking glass wars, 2010)
The people of Wonderland lose their creative drive when the power of the Heart Crystal is depleted, and when even Queen Alyss loses her powers, everybody takes comfort in the fact that Redd Heart is similarly disabled.